Determinación de las principales plagas y enfermedades del cultivo de vainita ((Phaseolus vulgaris L.), en el barrio de Santa Rosa, cantón Urcuquí, provincia de Imbabura - Ramos Anrango, Luis Ramiro (2018)
SUMMARY The unawareness of the use of agrochemicals in the cultivation of vainite causes economic losses and low yields in the same, to solve the problem was made in the sector of Santa Rosa, Urcuquí canton, Imbabura province, the identification of pests and diseases of greater incidence in the cultivation of the vainite. Using a survey of information through a survey of 15 people producing the area of the aforementioned crop. It was determined that the most severe disease in the crop is Anthracnose, Roya, and in less quantity it affects oidium, no less important than the other pathogens but its presence is low. Within the root system it was determined that Macrophomina is the most severe phytopathogenic agent, followed by Rhizoctonia. and root rot that, when associated, causes the death of the plant. Regarding pests, it was determined that the leafminer is the one that most affects the crop followed by whitefly, trips, red spider causing minor damage to the crop. In conclusion, the identification of pests and diseases affect the cultivation of vanilla allows us to make recommendations applying the integrated management of pests and diseases, and give constant monitoring to farmers' crops to reduce attacks and economic losses that cause pests not having a good control.